PEREMPUAN DALAM VIDEO GIM : Representasi Perempuan Dalam Dead or Alive 6 - Yuwono, Ardian Indro (Interaksi: Jurnal Ilmu Komunikasi, 2022)
In media industry, women are often represented as an object which cannot be separated from their sexual attractiveness. This kind of female sexualization also presents in various video games, such as Dead or Alive 6. Through this study, researcher tries to understand how female characters are represented in Dead or Alive 6 using Roland Barthes’s semiotic analysis. As for the result, four picked characters, Kasumi, Honoka, Marie Rose, and Momiji represent signs of sexualization such as their fashion, innocence, legal character but looks like an underage, or a paradox between sacredness and taboo. The sexualization of characters in Dead or Alive 6 turns the sexual traits of legal female characters as its selling point. Dead or Alive 6 sexualizes its female characters as part of its selling value by selling various expensive downloadable contents (DLC) in form of maid, bikini, or any other sexy costumes that has nothing to do with characters’ ability. The “water mode” and “soft mode” also can be considered as sexual exploitation towards the female characters as its selling point. It can be read that the game takes advantage from the players’ sexual fantasy as a goldmine.